Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Moldova - Yunus, Nur Rohim (UIN Jakarta, 2021)
Moldova is a unitary country located in the region of Southeastern Europe. Moldova's governmental structure incorporates features from both presidential and parliamentary systems, wherein the president wields overarching administrative authority while parliament assumes a significant part in shaping political determinations. The government of Moldova is comprised of three distinct parts of power, namely the executive, legislative, and judicial branches. The president, in their capacity as the head of state, assumes responsibility for foreign, defense, and security policy, whilst the prime minister assumes leadership of the administration and is accountable for the execution of policies. The Moldovan parliament, comprising two houses, possesses the jurisdiction to enact legislation, oversee the government, and execute additional legislative duties. Furthermore, Moldova possesses territories with distinct autonomy, namely Gagauzia and Transnistria, so introducing intricacy to the nation's governmental framework.